2016
DOI: 10.1590/2359-3997000000147
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal changes of serum adispin and visfatin levels in patients with type 2 diabetes after an overnight fast

Abstract: Objective: In order to elucidate the interrelationship of adipokines in glucose hemiostasis, we determined the concentration of visfatin and adipsin in blood samples in patients with type 2 diabetes and age-matched controls after an overnight fast. Subjects and methods: We enrolled 37 patients with known type 2 diabetes -21 males and 16 females, aged 62.95 ± 15.72 years and 43 controls-28 males and 15 females, aged 60.79 ± 12.67 years. Blood samples were collected after an overnight fast and routine biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
5
11
0
2
Order By: Relevance
“…Therefore, the discrepancies of the data might be due to the difference of race, degree of obesity, glycemic control, inclusion criteria and the detection methods. Furthermore, consistent with previous studies, the correlation analysis showed a negative correlation between serum adipsin and FPG and HbA1c. Meanwhile, there was a positive correlation between serum adipsin and HOMA‐β, AUC and AIR.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the discrepancies of the data might be due to the difference of race, degree of obesity, glycemic control, inclusion criteria and the detection methods. Furthermore, consistent with previous studies, the correlation analysis showed a negative correlation between serum adipsin and FPG and HbA1c. Meanwhile, there was a positive correlation between serum adipsin and HOMA‐β, AUC and AIR.…”
Section: Discussionsupporting
confidence: 91%
“…Speci cally we showed that adipsin was lower in T2D compared to NGT, which was similar to majority [40,[56][57][58] but not all [10,19] previously published research. In addition, this study showed that 2-hour post-glucose load adipsin was lower in T2D compared to NGT.…”
Section: Discussionsupporting
confidence: 90%
“…Adipsin level showed a decrease in diabetic patients compared to control group (13 ± 11.7 mg/dL vs.18.0 ± 13.4 mg/dL, P = 0.001). These results were confirmed by Legakis et al who reported that the circulating adipsin levels decreased in patients with T2DM (74.30 ± 12.51 pg/mL vs. 117.1 ± 5.03 pg/mL, P < 0.0001) (19). It is also reported that adipsin is a protein of adipose cells, but paradoxically declines in many animal models of obesity and diabetes (9).…”
Section: Discussionsupporting
confidence: 68%
“…Adipose tissue acts not only as energy storage in the body, but also as an endocrine organ that secretes different hormones or adipokines, which circulate in distinct target receptors in many tissues. These adipokines seem to contribute in the pathogenesis of T2DM (19).The different metabolic profile of the adipokines such as fetuin-A and adipsin improve the possible role of the adipose tissue in the energy metabolism and glucose homeostasis in T2DM. Different factors may contribute to fetuin-A regulation in relationship with the pathophysiological consequence in T2DM.…”
Section: Discussionmentioning
confidence: 99%